Antifungal Activity of Jatropha curcas Pericarps and leaves Extracts - Ishak, Nur Diyana; Jusoh, Ismail; Assim, Zaini (International Congress ofthe Malaysian Society for Microbiology, 2011)
Jatropha curcas usually have a variety of uses especially in traditional medicine such as to relieve pain and skin disease. The oil and aqueous extracts from all parts of plants have the potential to act as insecticide. The objectives of this study were to determine toxicity methanol extracts of J. curcas leaves and pericarps; and to analyse the chemical composition of J. curcas pericarps and leaves. Various concentration levels of methanol crude extracts of pericarps and leaves (50 jJg/mL, 100 J,Jg/mL, 250 IJ9ImL, 500 J.lg/mL and 1000 jJg/mL) were prepared. The extracts were subjected to analysis on capillary GC/MS to determine the chemical constituents. Antifungal activities were determined by using paper disc diffusion method and the antifungal activities were evaluated after 72 h of incubation period. This study revealed that the leaves and peri carp extracts possessed Significant activities against Trametes versicolor, Gleophyllum trabeum and Chaetomium g/obosum. Leaves and pericarps extracts showed antifungal activity against T. versicolor at 500 JIg/mL At the concentration of 1000 l1g/mL leaves and pericarps extracts, it exhibited weak to moderate antifungal activity for T. versicolor, G. trabeum and C. globosum. The major components of hexane and dichloromethane (DeM) soluble fraction of methanol extract from pericarps and leaves were 9-octadecanoic acid, hexacosane, 1,2 benzenedicarboxylic acid mono 2-ethylhexyl ester and octacosane. The results suggest that J. curcas methanol extracts have weak to moderate antifungal activity against T. versicolor, G. trabeum and C. globosum. Further studies on antifungal and antibacterial activities are required in order to diversify the utilization of J. curcas plant.